Education and Lifetime Patterns of Unemployment - Nickell, Stephen (Journal of Political Economy, 1979)
The relationship between education and unemployment incidence, although theoretically clear-cut, has rarely been quantified. Some estimates of this relationship are obtained for Britain, and these are split into the impact of schooling and qualifications on the probability of entering unemployment and on the expected duration of spells within that state. Finally, estimates of the rate of return to schooling are adjusted to take account of unemployment incidence.